Synthesis of allyl sulfones bearing urethane groups as efficient addition-fragmentation chain transfer agents for the development of low-shrinkage composites. (5th September 2021) - Lamparth, Iris; Wottawa, David; Angermann, Jörg; Fässler, Pascal; Liska, Robert; Catel, Yohann
Graphical abstract: Highlights: Synthesis of four innovative addition-fragmentation chain transfer agents bearing urethane groups. Evaluation of the rheological behavior using real time-NIR-photorheology. Formulation and characterization of innovative low-shrinkage dental composites exhibiting excellent mechanical properties. Influence of the urethane group on the mechanical properties of the tested materials. Abstract: Polymerization shrinkage represents one of the major drawbacks of dental composites. The incorporation of chain transfer agents into dental formulations is an efficient technology that enables a strong reduction of the shrinkage stress. In this contribution, the synthesis of four new addition-fragmentation chain transfer (AFCT) agents bearing urethane groups is described. These compounds were easily synthesized in three steps. Real-time (RT)-NIR photorheology measurements were performed to evaluate rheological behavior (i.e. time of gelation) and chemical conversion (i.e. double bond conversion at the gel point, final double bond conversion) of dimethacrylate resins containing the synthesized transfer agents. Composites based on these AFCT agents provide good mechanical properties as well as low shrinkage force. The presence of the urethane group results in a significant improvement of the mechanical properties. The addition of urethane AFCT agents to dental composites is an efficient technology that enables the formulation of low shrinkage materials having high flexural strength and modulus.